2016
DOI: 10.1158/1940-6207.capr-16-0033
|View full text |Cite
|
Sign up to set email alerts
|

Association between Circulating Vitamin D Metabolites and Fecal Bile Acid Concentrations

Abstract: While hydrophobic bile acids have been demonstrated to exhibit cytotoxic and carcinogenic effects in the colorectum, ursodeoxycholic acid (UDCA) has been investigated as a potential chemopreventive agent. Vitamin D has been shown to play a role in both bile acid metabolism and in the development of colorectal neoplasia. Employing a cross-sectional design, we sought to determine whether baseline circulating concentrations of the vitamin D metabolites 25(OH)D and 1,25(OH)2D were associated with baseline fecal bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The ligation of vitamin D with its cytosolic receptor results in increased protein synthesis as well as phosphorylation of intracellular proteins enhancing the kinetics of smooth muscle contraction [31][32][33]. In addition, activated vitamin D receptors in mice and humans increase hepatic expression of CYP3A4, a cytochrome P450 enzyme that decreases bile acid hydrophobicity, and thus toxicity, of bile acids [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The ligation of vitamin D with its cytosolic receptor results in increased protein synthesis as well as phosphorylation of intracellular proteins enhancing the kinetics of smooth muscle contraction [31][32][33]. In addition, activated vitamin D receptors in mice and humans increase hepatic expression of CYP3A4, a cytochrome P450 enzyme that decreases bile acid hydrophobicity, and thus toxicity, of bile acids [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The ligation of vitamin D with its receptor results in increased kinetics of muscle contraction (Boyan et al 2003, Ceglia 2008. Another added benefit of vitamin D is that it increases expression of CYP3A4 in mice and humans, a cytochrome P450 enzyme that decreases bile acid hydrophobicity (Makishima et al 2002, Thompson et al 2002, Nishida et al 2009, Jacobs et al 2016. A recent observational study found that decreasing serum 25-hydroxyvitamin(OH) D concentrations was associated with a more advanced developmental stage of GBM type determined by ultrasonography (Jaffey et al 2020).…”
Section: Gall Bladder Mucocelementioning
confidence: 99%
“…2009, Jacobs et al . 2016). A recent observational study found that decreasing serum 25‐hydroxyvitamin(OH)D concentrations was associated with a more advanced developmental stage of GBM type determined by ultrasonography (Jaffey et al .…”
Section: Gall Bladder Mucocelementioning
confidence: 99%
“…Therefore, 56 articles were further assessed for inclusion and 8 articles were excluded (3 included cases with hyperplastic polyps to calculate the risk and 5 did not describe detailed information of CRA history). Finally, 48 eligible articles were included in this systematic review and meta-analysis: 28 articles evaluated the association of vitamin D intake on the risk of CRC precursors occurrence (incidence/recurrence) (27, 28, 39-64), 26 articles evaluated the association between circulating 25(OH)D level and risk of CRC precursors occurrence (incidence/recurrence) (28,39,43,47,50,57,(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84). Supplementary Table 4 summarized the main characteristics of the included studies.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%